A Conceptual Study of Medo Dusthi w.s.r. to Dyslipidemia in Ayurveda - Prakash, Ved; Parashar, Deepti; Sangeeta (International Research Journal of Ayurveda & Yoga, 2024)
As the Indian economy grows, the epidemic of Medo Roga has spread across the country. The food we eat on a daily basis contributes to our health. However, many people’s desire to eat more and exercise less is hastening the spread of the Medo Roga. Obesity is spreading in the modern day due to lifestyle changes and increased consumption of junk food combined with a stressful lifestyle. According to recent studies, high cholesterol is present in 25-30% of urban and 15-20% of rural subjects. This prevalence is lower in low-income countries than in high-income countries. This negative health consequence could be the cause of a variety of lifestyle disorders such as dyslipidemia, hyperlipidemia, malnutrition, and osteoarthritis, among others. In today’s fast-paced world, dyslipidemia is a major lifestyle disorder. The ramifications of Medo Vikriti and its dangers have been well documented in our classics. Medoroga is primarily an Agni imbalance caused by a variety of etiological causes, including Aaharatmak, Viharatmak, Mansik, and others such as Bijabhava (hereditary). There is no such phrase as dyslipidemia in Ayurveda texts, however the qualities of Sneha Dravya are defined as Medodhatu in Ayurveda.